Learning Strategies and Challenges of EFL Learners in Enriching English Vocabularies - Fuadi, Adillah Suroyyah; Ningrat, Chelsea Chahya; Williyan, Aldha (Foreign Language Instruction Probe, 2023)
Challenges always exist in learning any English skills, including vocabulary building. This leads to the fact that EFL learners still do not know what strategies can be used to enrich English vocabularies. This qualitative study therefore aims to investigate what strategies are used by EFL learners and the challenges experienced by them in enriching and memorizing vocabularies. To achieve those objectives, this research categorizes the respondents into three groups, namely the first, second and third grades of senior high school. They are all interviewed in a semi structured way to find out in-depth data. The analyses reveal that the respondents employ various strategies to enrich the English vocabularies. The majority of the first grade respondents use the strategy of watching movies, reading English books and saying English words repeatedly. Then, the second grade respondents prefers to use the strategy of saying the English words repeatedly, watching movies and reading articles. Lastly, the third grade of the respondents use the strategy of watching movies and listening to music. This indicates that enriching vocabulary not only requires formal strategies in the classroom but also informal strategies outside the classroom.